Mapping white identity terrorism and racially or ethnically motivated violent extremism: a social network analysis of online activity - Williams, Heather J. (RAND, 2022)
CHAPTER ONE: Overview -- CHAPTER TWO: Literature Review -- CHAPTER THREE: Network Analysis of WITM and REMVE -- CHAPTER FOUR: Country Case Studies -- CHAPTER FIVE: Conclusion and Opportunities for Impact -- APPENDIX A: White Genocide Terms -- APPENDIX B: Triangulating Platform Antisociality: Dark Triad by Sentiment -- APPENDIX C: Longitudinal Analysis of Highest-Scoring Dark Triad Communities Across Platforms -- APPENDIX D: Simulations of Deplatforming or Other Counter-REMVE Action in Online Networks -- APPENDIX E: Religion and Christianity Keywords Applied to Twitter -- APPENDIX F: Dendrogram of Lexical Similarities by Location on Twitter.